Research on Treasury Management of Dairy Enterprises under the Background of Intelligent Finance——Take Z Dairy Group as an Example - Lan, Zhengzuo (Journal of Global Economy, Business and Finance, 2024)
In the context of global economic integration and the development of the Belt and Road Initiative, the flow and integration of high-quality resources in the global dairy industry chain are accelerating. With the rapid internationalization of China's dairy industry, local dairy companies need to accelerate technological progress, reduce operating costs, and expedite brand internationalization. The globalization of fund management for Chinese dairy enterprises has become an unavoidable issue. In recent years, major domestic companies have gradually established financial sharing centers relying on technologies such as big data and cloud computing. Intelligent finance, as a combination of intelligent technology and financial work, is leading financial transformation in this environment, ushering financial work into the intelligent era. This paper studies the treasury management of Chinese dairy enterprises, taking Z Dairy Group as an example. It explores the construction and implementation effects of Z Dairy's treasury system under the background of intelligent finance, analyzes the issues in Z Dairy's intelligent treasury management, and provides relevant suggestions. This aims to offer insights and inspiration for fund management of Chinese dairy enterprises in the context of globalization and digitalization, and to promote the scientific development of intelligent treasury management in corporate groups.